The professional development of teaching staff in UK universities. National considerations and insights into practices at one university - Berthiaume, Denis; Morrison, Mary (BzL - Beiträge zur Lehrerinnen- und Lehrerbildung, 2009)
In this article, we examine the link between national measures to encourage the professional development of university teaching (academic) staff and the practices of higher education institutions (HEIs) in the United Kingdom. More specifically, we look at how one UK institution (the University of Southampton) has responded to the demands of the national standards set with regards to teaching and learning. The main argument of the article is that a national context which encourages and values the development of pedagogical knowledge and skills by university teaching staff is essential for HEIs to adopt institutional policies and practices in that regard. The article ends with some thoughts for the future development of university teaching and learning in Switzerland.